Delirium in critical care - Page, Valerie J.; Ely, E. Wesley (Cambridge : Cambridge University Press, 2015)
The fully updated second edition of this popular handbook concisely summarises all current knowledge about delirium in critically ill patients and describes simple tools the bedside clinician can use to prevent, diagnose and manage delirium. Chapters discuss new developments in assessing risk and diagnosis, crucial discoveries regarding delirium and long-term cognitive outcomes, and dangers of sedation and death. Updated management advice reflects new evidence about antipsychotics and delirium. This book explains how to minimise the risks of delirium, drugs to avoid, drugs to use and when to use them, as well as current theories regarding pathophysiology, different motoric subtypes leading to missed diagnosis, and the adverse impact of delirium on patient outcomes. While there are still unanswered questions, this edition contains all the available answers. Illustrated with real-life case reports, Delirium in Critical Care is essential reading for trainees, consultants and nurses in the ICU and emergency department.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Critical care; Delirium